2013
DOI: 10.1089/jop.2012.0179
|View full text |Cite
|
Sign up to set email alerts
|

Baicalein Protects Against Retinal Ischemia by Antioxidation, Antiapoptosis, Downregulation of HIF-1α, VEGF, and MMP-9 and Upregulation of HO-1

Abstract: Purpose: Retinal ischemia-associated ocular disorders are vision threatening. This study examined whether the flavonoid baicalein is able to protect against retinal ischemia/reperfusion. Methods: Using rats, the intraocular pressure was raised to 120 mmHg for 60 min to induce retinal ischemia. In vitro, an ischemic-like insult, namely oxidative stress, was established by incubating dissociated retinal cells with 100 mM ascorbate and 5 mM FeSO 4 (iron) for 1 h. The rats or the dissociated cells had been pretrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
52
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 25 publications
6
52
0
Order By: Relevance
“…studied in the context of angiogenesis prevention were reported to inhibit HIF-1a (as reviewed in Fernando et al, 2015). Flavone baicalein was able to down-regulate HIF-1a in ovarian cancer cells (Chen et al, 2013) or in retinal cells, where it protects against retinal ischemia/reperfusion (Chao et al, 2013). Quercetin was shown to reduce the activity of HIF-1a in HCT116 cancer cells .…”
Section: The Regulation Of Cbr1 Transcript By Polyphenolsmentioning
confidence: 99%
“…studied in the context of angiogenesis prevention were reported to inhibit HIF-1a (as reviewed in Fernando et al, 2015). Flavone baicalein was able to down-regulate HIF-1a in ovarian cancer cells (Chen et al, 2013) or in retinal cells, where it protects against retinal ischemia/reperfusion (Chao et al, 2013). Quercetin was shown to reduce the activity of HIF-1a in HCT116 cancer cells .…”
Section: The Regulation Of Cbr1 Transcript By Polyphenolsmentioning
confidence: 99%
“…As an important downstream mediator within TLR4/NF-κB signaling pathway, a body of evidences have indicated that MMP-9 participates in the BBB disruption and brain edema formation after SAH (Feiler et al, 2011). Recently, some studies suggested that baicalein can inhibit MMP-9 (Chao et al, 2013;Lee and Lee, 2012). In this study we assessed the effect of baicalein on MMP-9 expression.…”
Section: Discussionmentioning
confidence: 94%
“…HO-1 plays an important role in protecting the cardiovascular system. HO-1 protects endothelial cells and cardiomyocytes as an antioxidant [33]. HO-1 also directly inhibits cardiomyocyte hypertrophy and reduces the ratio of left ventricular weight to body weight.…”
Section: Discussionmentioning
confidence: 99%